Models of Management Morality for the New Millennium - Carroll, Archie B. (Business ethics quarterly, 2001)
This paper is the presidential address to the Society for Business Ethics presented during its annual meeting in Chicago, Illinois, on August 7, 1999. The paper discusses three models of management morality and considers their applicability for thinking about business ethics in the new millennium. The moral management model, in particular, is discussed in contrast to the moral market model, which was presented in the previous year’s presidential address by John Boatright. Immoral Management, Moral Management, and Amoral Management are considered and two hypotheses about the presence of amorality within the management population and individual managers are reflected upon.